Performance e imagem técnica: o processo criativo da "Rainha de Copas e suas 7 primas invejosas" - Brito, Adriane Gomes de (2012)
The objective of this work is to research and produce a critical thinking about the use of technological apparatus to produce the technical image. The proposal of this research is to create and experiment a digital and technological game using the body and the technical basis of theatre and circus as receptive and interactive environments, through multimedia equipments for the setting of the corporal/performative system and its relations with technology. Some authors were fundamental in this research process: it is necessary to talk about Vilém Flusser e Marshall McLuhan, that present a critical and contemporary thinking about the body and its relations with the technological apparatus, and about Ivani Santana, Henri-Pierre Jeudy, Antonio Damásio, Arlindo Machado e Renato Cohen, authors that grounded the idea of performance art and technical image in the relations with the creative body.The work draws attention to the vulnerability of digital art, to how the body has turned away or has set down in this new digital context, to how communication and continuous use of internet change the everyday and people's life and how this reflects in art and in the life of people that belong to this new generation on which technology is omnipresent. Accordingly, it ends recognizing the existence of new rites and myths in this contemporary bodies, realizing that the games are using the myths to compose its stories the japanese always used some western myth to create their games.The perspective of the methodology used along the experiencing process was a documentary about the setting process and the realization of the show Rainha de Copas e suas 7 primas invejosas (The Queen of Hearts and her 7 envious cousins). The documentary will have at most 20 minutes and will be accompanied by verbal-visual images and photographies, captured along the research. Moreover, were included in the work actions in shape of happening, performances and open experiences, finally resulting in the multimedia show Rainha de Copas e suas 7 primas invejosas.It is important to affirm that the practical and philosophical experience promoted not just the development of a techno-performance's product or a digital designer's technique, but also promoted a critical thinking about the body in contact with images and the idea of how bodies turn into dragonflies when in contact with the spotlight